Clinical Nursing Education: Using the FICA Spiritual History Tool to Assess Patients' Spirituality. Issue 4 (July 2016) - Williams, Margaret G.; Voss, Autumn; Vahle, Barb; Capp, Sheila
Abstract : Nursing students often find it difficult to address spirituality in clinical practice. The purpose of this study was to examine the effect of students' use of the FICA Spiritual History Tool during clinical practice on their own spirituality and comfort with the provision of spiritual care. The students (N = 31) completed the Spirituality and Spiritual Care Rating Scale at the beginning and end of the semester, which revealed changes, although not statistically significant, in students' spirituality, religiosity, and their provision of spiritual care.